Fios de roca e tramas sentimentais: personagens tecelãs em O Continente, Os Sinos da Agonia e O Voo da Guará Vermelha - Piaceski, Daiana Patrícia Follman Pasquim (2017)
In the spinning wheel, in the loom, in the interlacing of threads for the construction of a text (like telling a lullaby to the children) rests, almost always, the hands of the women; Extrapolating the literal understanding of sewing, darning, weaving, spinning, the literary text often presents them metaphorically, as a feminine artifice to overcome or subvert the prevailing patriarchal order, a backbone issue on a theoretical basis undertaken in this research. As a theoretical corpus, the foundation for this work in História das Mulheres do Brasil, Histórias íntimas, Casa Grande & Senzala, Um Teto todo Seu, O Segundo Sexo, and others. The fictional texts analyzed here, O Continente (1949), Os Sinos da Agonia (1974) and O voo da Guará Vermelha, (Objetiva, 2005), present three different profiles of women corresponding, in one way or another, to a Archetype - definition by Carl Jung (1976) - of the weaver woman, each emanating different desires. Following the heart is Ana Terra, within text of Erico Verissimo (1905-1975), As well as the women in their line of succession, Bibiana and Maria Valéria; Taken by her instincts of femme fatale comes Malvina, by Autran Dourado (1926-2012); Facing the social impositions, an argument deeply rooted in the female figure - emerges the seropositive prostitute Irene, a character written by Maria Valéria Rezende (1942). It is analyzed a construction of female people who, molded within an achetypal plane, corresponds the figure of the weaver woman and, thus, they manage to be "owners of their destinies", even under a patriarchal order, through their actions, your desires, your influences. Searches related to the main Brazilian literary histories, such as one organized by Afrânio Coutinho, Alfredo Bosi, Carlos Nejar and others, foundations for the explanation about the critical resourses of the works, besides the literary articles printed and online. In addition, an exclusive interview made on the telephone, which the writer Maria Valéria Rezende gave directly to the author. The work has theoretical, bibliographical and literary fundamentals: it begins with a patriarchy's theory, followed with a critical resourses of the works, crosses the archetypes of the collective unconscious and Greek mythology, in order to arrive at the literature works, where some relations of meaning which fostered as discussions about the theme. The analysis reveals the contours given to weaver characters, contextualizing them, thematically and historically, inside the patriarchal universe to which they are submitted. It shows how such women have created subterfuges to place themselves in this universe governed by man, and even, as they do to control it.